Quantitative Assessment of Potential Epidemic Hazard of Mass Events with International Participation and Methodology Approbation in the Context of Universiade-2013 - G. G. Onishchenko; M. A. Patyashina; S. K. Udovichenko; A. V. Toporkov; E. V. Kouklev; V. P. Toporkov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2015)
Put forward is a methodology for quantitative assessment of potential epidemic hazard (PEH) as regards mass events with international participation in terms of the relevant infectious diseases capable of (in compliance with IHR, 2005) inducing emergency situation of sanitary epidemiological character. It is established that PEH is an aggregate risk of infection importation by incoming contestants and visitors and of its dissemination across the mass even location. As a result of PEH level differentiation identified have been four following grades: high, medium, low and minimum. Calculated has been a rate of PEH for the XXVI Worldwide Summer Universiade in Kazan, 2013, exemplified by such infectious disease as cholera.